Requirements for Professional Competence Formation of Environmentalists in the Society Transition to Sustainable Development - Bogoliubov, Volodymyr; Bogoliubova, Nataliia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
This article is dedicated to reasoning of requirements formation for professional competence system of future environmentalists in the society transition to sustainable development. It is proposed to form professional competence based on the analysis of production functions of future environmentalist. It is taken into account the need to ensure professional mobility of graduates. It is examined different variants of implementation of the education elements for sustainable development into formal education system.
Keywords: education system; sustainable development; professional competence; production functions